Integrasi Nilai-Nilai Karakter Abad 21 (4c: Critical Thinking, Creativity, Communication, Collaboration) Melalui Metode Deep Learning Dalam Pembelajaran Pendidikan Kewarganegaraan di SMK - Anis Silfiyah; Taufiq Harris; M. Furqon Wahyudi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Educational challenges in the 21st century have become increasingly complex in line with the rapid development of technology and artificial intelligence, requiring educational institutions to prepare graduates who are not only proficient in technical skills but also possess strong character and higher-order thinking competencies. Vocational High Schools (Sekolah Menengah Kejuruan/SMK) as vocational education institutions are required to integrate 21st-century character values, including critical thinking, creativity, communication, and collaboration (4C), into the learning process. This study aims to examine the implementation of the integration of 4C character values through the application of the deep learning method in Civic Education (Pendidikan Kewarganegaraan/PKn) learning at SMKN 2 Sukorejo, as well as to identify the supporting and inhibiting factors in its implementation. This research employed a qualitative approach with a descriptive design. Data were collected through observations, interviews, and documentation. The results indicate that the application of the deep learning method in Civic Education learning is able to facilitate students in critically analyzing civic issues, fostering creativity in formulating solutions, enhancing communication skills, and strengthening collaboration through contextual and collaborative learning. Supporting factors include teacher readiness, a conducive school climate, and the relevance of learning materials, while the constraints encountered include limited instructional time and differences in students’ abilities. This study confirms that the deep learning method has the potential to serve as a strategic approach to strengthening 21st-century character development among vocational high school students.